A scale and corrosion inhibitor for seawater circulating cooling water

CN121292684BActive Publication Date: 2026-10-16JIANGSU KELIEN WATER PURIFYING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511733527.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-10-16
Estimated Expiration
2045-11-24

AI Technical Summary

Technical Problem

这种非靶向的防护模式,导致在关键设备表面的有效组分浓度不足,为达到预期的抑制效果,必须提高整体投加量,这不仅增加了运行成本,也未能实现对关键设备的高效防护

Benefits of technology

1.本发明提供的阻垢缓蚀剂具有优异的贮存稳定性,通过将带相反电荷的阴、阳离子预聚体在聚氧乙烯-聚氧丙烯嵌段共聚物存在下进行共组装,形成一种动力学稳定的聚电解质复合物,以物理方式将锌盐与膦酸盐等化学性质不相容的组分隔离于一个均相体系内,有效避免了它们在产品配制及贮存过程中的直接接触与沉淀反应,确保了产品在长期存放后的性能稳定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005702838270000091
    Figure BDA0005702838270000091
  • Figure BDA0005702838270000101
    Figure BDA0005702838270000101
  • Figure BDA0005702838270000111
    Figure BDA0005702838270000111
Patent Text Reader

Abstract

The present application relates to the field of water treatment, discloses a kind of scale and corrosion inhibitor for seawater circulating cooling water, by phosphonic acid group grafting maleic anhydride-acrylic acid copolymer, hydroxyethylidene diphosphonic acid, aminotri (methylene) phosphonic acid, N,N-diethylaminomethyl-benzotriazole, gamma-aminopropyl triethoxysilane, zinc salt and polyoxyethylene-polyoxypropylene block copolymer are made into raw materials.The core of the present application is that each raw material component is formed into a temperature-sensitive polyelectrolyte complex by self-assembly process.The complex uses the cloud point effect of block copolymer, and is stably dispersed at low temperature, and phase transition occurs on high-temperature heat exchange surface and preferentially deposits, to realize the targeted and efficient delivery of multiple active components.The present application solves the problem of poor compatibility and stability of traditional compounded medicaments, and the product has excellent storage stability and can achieve efficient corrosion and fouling control under high temperature and high salinity conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment technology, and in particular to a scale and corrosion inhibitor for seawater circulating cooling water. Background Technology

[0002] Seawater cooling systems are widely used in industries such as power, chemical, and shipbuilding. The high concentrations of chlorides, sulfates, and calcium and magnesium hardness ions in seawater pose a continuous challenge of corrosion and scaling. Therefore, developing scale and corrosion inhibition technologies that can operate stably in this environment is one of the core issues in this field.

[0003] To address these challenges, existing technologies often employ compound water treatment agents. However, the chemical incompatibility between the functional components in these agents remains a technical hurdle. For example, when cationic zinc salts, acting as corrosion inhibitors, coexist with anionic organophosphonates, acting as scale inhibitors, they readily react to form insoluble precipitates. This phenomenon not only reduces the effective concentration of the active components but also triggers secondary fouling, affecting the storage stability and performance of the formulation.

[0004] Furthermore, conventional chemical dosing methods maintain a certain concentration throughout the water body, but scaling and corrosion processes mainly occur at high-temperature solid-liquid interfaces such as heat exchangers. This non-targeted protection mode results in insufficient concentration of effective components on the surface of critical equipment. To achieve the desired inhibition effect, the overall dosage must be increased, which not only increases operating costs but also fails to achieve efficient protection for critical equipment.

[0005] Meanwhile, in complex systems containing multiple metals, existing agents struggle to provide comprehensive synergistic protection. The effectiveness of some polymer scale inhibitors decreases in high-hardness water, while commonly used zinc salt corrosion inhibitors are effective for carbon steel but offer insufficient protection against copper alloys. This makes it difficult to form a stable protective film in mixed-material systems that can simultaneously inhibit multiple types of fouling and protect different metals, thus affecting the overall reliability and service life of the system. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a high-efficiency scale and corrosion inhibitor for seawater circulating cooling water that can achieve targeted delivery and synergistic control of corrosion and scaling on the surface of heat exchange equipment in a high-temperature, high-salinity seawater cooling water system.

[0007] To solve the above-mentioned technical problems, the present invention provides a scale and corrosion inhibitor for seawater circulating cooling water, adopting the following technical solution: A scale and corrosion inhibitor for seawater circulating cooling water is made from raw materials comprising the following parts by weight: 100-115 parts of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer; 28-40 parts of hydroxyethylidene diphosphonic acid; 50-75 parts of aminotrimethylenephosphonic acid; 8-15 parts of N,N-diethylaminomethyl-benzotriazole; 30-45 parts of γ-aminopropyltriethoxysilane; 40-55 parts zinc salt; 20-35 parts of polyoxyethylene-polyoxypropylene block copolymer.

[0008] By employing the above technical solution, this invention co-assembles various scale inhibitors and corrosion inhibitors with different functions through a specific preparation process to form a kinetically stable temperature-sensitive polyelectrolyte complex (T-PEC) colloidal dispersion system. The core innovative mechanism of this system lies in its environmental responsiveness, the specific process of which is described below: Construction of the complex: First, anionic components such as phosphonic acid grafted with carboxyl and phosphonic acid groups, maleic anhydride-acrylic acid copolymer, hydroxyethylidene diphosphonic acid, and aminotrimethylene phosphonic acid are premixed with N,N-diethylaminomethyl-benzotriazole to form a negatively charged anionic polyelectrolyte prepolymer.

[0009] Simultaneously, γ-aminopropyltriethoxysilane is hydrolyzed under acidic conditions to generate a positively charged protonated amino group (-NH3). + ) and silanol groups (-Si-OH) with complexing ability. Then, a zinc salt is introduced, and zinc ions (Zn) are formed. 2+ It complexes with the above groups to form a stable cationic complex prepolymer.

[0010] Finally, in the presence of the polyoxyethylene-polyoxypropylene block copolymer as the co-assembly medium, the components undergo controlled self-assembly through electrostatic attraction between the anionic and cationic prepolymers, ultimately forming the temperature-sensitive polyelectrolyte composite. This block copolymer acts as a steric stabilizer in the composite, preventing the direct precipitation of incompatible components.

[0011] Targeted release mechanism: In circulating water bodies at lower temperatures (such as pipes and pools), the complex is dispersed in the water in a stable colloidal form, with each active component bound inside the colloidal structure, maintaining a low free concentration.

[0012] When circulating water flows over the surface of high-temperature equipment such as heat exchangers, the local water temperature rises and exceeds the cloud point temperature of the polyoxyethylene-polyoxypropylene block copolymer. This causes a phase transition in the block copolymer, with the molecular chains changing from a hydrophilic state to a hydrophobic state and contracting, leading to the disruption of the overall colloidal structure of the composite.

[0013] The unstable complex preferentially adsorbs and deposits at the high-temperature solid-liquid interface, thereby achieving the in-situ release of high concentrations of scale-inhibiting and corrosion-inhibiting active components on the heat exchange surface that needs the most protection, realizing targeted and efficient delivery of active substances.

[0014] Therefore, the technical solution of the present invention will provide a variety of incompatible active components, solve the problems of poor stability of conventional compound drugs and insufficient concentration of effective ingredients in key areas, and improve the overall protective performance under harsh working conditions.

[0015] Preferably, the phosphonic acid-grafted maleic anhydride-acrylic acid copolymer is obtained by polymerization of maleic anhydride and acrylic acid as comonomers, wherein the molar ratio of maleic anhydride to acrylic acid in the comonomer is (2-4):(6-8).

[0016] By adopting the above technical solution, the setting of this molar ratio ensures that the copolymer backbone has sufficient rigid structure derived from maleic anhydride units and strong calcium ion chelating sites, while the acrylic acid units provide good water dispersibility. The synergistic effect of the two optimizes the scale inhibition performance and system compatibility of the polymer.

[0017] Preferably, the mass ratio of the total solid content of the phosphonic acid-grafted maleic anhydride-acrylic acid copolymer to that of the hydroxyethylidene diphosphonic acid and the aminotrimethylene phosphonic acid is (0.85-1.4):1.

[0018] By adopting the above technical solution, copolymers within this molecular weight range possess both excellent scale inhibition and dispersion capabilities and suitable viscosity. If the molecular weight is too low, the scale inhibition efficiency and film-forming properties decrease; if the molecular weight is too high, the water dispersibility deteriorates, which is detrimental to the formation of a stable complex.

[0019] Preferably, the method for preparing the phosphonic acid-grafted maleic anhydride-acrylic acid copolymer includes: after copolymerizing maleic anhydride with acrylic acid, adding phosphorous acid and formaldehyde to carry out a grafting reaction, thereby introducing phosphonic acid groups onto the copolymer molecular chain.

[0020] By adopting the above technical solution, the phosphonic acid group introduced on the polymer side chain is not only a highly efficient scale-inhibiting functional group, but also provides additional negative charge sites, which enhances the electrostatic interaction between it and the cationic complex prepolymer, and is conducive to the formation of a more stable polyelectrolyte complex.

[0021] Preferably, the N,N-diethylaminomethyl-benzotriazole is prepared by benzotriazole, diethylamine and formaldehyde under Mannich reaction conditions.

[0022] By adopting the above technical solution, benzotriazole is modified by Mannich amine methylation, which improves its solubility and dispersibility in the aqueous system, enabling it to be uniformly integrated into the anionic prepolymer. This ensures that it can be targeted and delivered to the surface of copper alloys such as brass along with the entire composite system, thereby exerting an effective corrosion inhibition effect.

[0023] Preferably, the zinc salt is zinc sulfate or zinc sulfate heptahydrate.

[0024] By adopting the above technical solution, zinc sulfate is a commonly used and cost-effective zinc source in industry, which can stably provide zinc ions as a cathode corrosion inhibitor.

[0025] Preferably, the turbidity point temperature of the polyoxyethylene-polyoxypropylene block copolymer in aqueous solution is 35-50℃.

[0026] By adopting the above technical solution, the cloud point temperature range is highly matched with the operating characteristics of industrial circulating cooling water systems. The main system water temperature is typically below 35°C, while the heat exchanger surface temperature is generally above 40°C. This setting ensures that the complex remains stable in the main circulation pipeline, triggering a response only in the target area (heat exchange surface), achieving precise targeted control.

[0027] Preferably, the solid content mass ratio of hydroxyethylidene diphosphonic acid to aminotrimethylene phosphonic acid is 1:(1.6-2.1). By adopting the above technical solution, hydroxyethylidene diphosphonic acid and aminotrimethylene phosphonic acid are two organophosphonates with complementary properties. When combined within this specific mass ratio range, they can produce a synergistic effect and exhibit excellent inhibition effects on various types of scale such as calcium carbonate and calcium phosphate.

[0028] Preferably, the weight ratio of the γ-aminopropyltriethoxysilane to the zinc salt is 1:(1.2-1.5). By employing the above technical solution, this weight ratio ensures that the hydrolyzed γ-aminopropyltriethoxysilane provides sufficient coordinating groups to form a stable complex with zinc ions. This prevents free zinc ions from directly reacting with components such as phosphonates to form precipitates, and also constitutes a positively charged cationic prepolymer with corrosion-inhibiting properties, which is crucial for subsequent electrostatic self-assembly steps.

[0029] Preferably, the raw material components form a thermosensitive polyelectrolyte composite with the polyoxyethylene-polyoxypropylene block copolymer as the co-assembly medium.

[0030] By adopting the above technical solution, the final form of the product is clarified. This composite structure is the physical basis for achieving all the technical effects of this invention; it organizes the individual chemical components into a functionally synergistic and environmentally responsive whole.

[0031] In summary, the present invention has at least one of the following beneficial technical effects: 1. The scale and corrosion inhibitor provided by this invention has excellent storage stability. By co-assembling anionic and cationic prepolymers with opposite charges in the presence of polyoxyethylene-polyoxypropylene block copolymer, a kinetically stable polyelectrolyte complex is formed. This physically isolates chemically incompatible components such as zinc salts and phosphonates in a homogeneous system, effectively avoiding their direct contact and precipitation reaction during product formulation and storage, and ensuring the product's performance stability after long-term storage.

[0032] 2. The product of this invention achieves targeted protection of the surface of heat exchange equipment, improving scale inhibition and corrosion inhibition efficiency. Utilizing the thermosensitive properties of the polyoxyethylene-polyoxypropylene block copolymer in the composite, when the agent flows through the high-temperature heat exchange surface, the composite undergoes a phase transition and becomes unstable due to the local temperature exceeding its cloud point, preferentially depositing at the high-temperature solid-liquid interface. This process efficiently enriches multiple active components such as phosphonic acid graft copolymer, organophosphonates, zinc salts, and copper corrosion inhibitors in the areas most prone to scaling and corrosion, thereby achieving a synergistic and efficient inhibition effect with a relatively low overall dosage concentration.

[0033] 3. This invention provides broad-spectrum and synergistic protection against various materials and fouling through the scientific compounding and structure of multiple components. The phosphonate-grafted maleic anhydride-acrylic acid copolymer, compounded with various organophosphonates, has excellent inhibition and dispersing ability against hard scale such as calcium carbonate. The complex formed by γ-aminopropyltriethoxysilane and zinc salt acts as a cationic corrosion inhibitor, which can form a protective film on the metal surface. N,N-diethylaminomethyl-benzotriazole provides special protection for copper alloy materials. The components work synergistically under the targeted release mechanism to achieve comprehensive and long-term corrosion and scaling control of mixed material systems such as carbon steel and copper alloys. Detailed Implementation

[0034] Preparation Examples 1-3: Preparation Example 1: Preparation of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA): Add 300g of deionized water to a 1000mL four-necked flask equipped with a mechanical stirrer, thermometer, reflux condenser, and constant-pressure dropping funnel. Start the stirrer and heat the flask to 80°C. Mix 60g of maleic anhydride and 110g of acrylic acid (monomer molar ratio approximately 3:7) thoroughly beforehand; dissolve 15g of ammonium persulfate in 50g of deionized water to prepare an initiator solution. Place the mixed monomers and initiator solution into two separate constant-pressure dropping funnels and add them dropwise to the reaction flask at a uniform rate over 3 hours. After the addition is complete, continue the reaction at 80°C for 2 hours. After the reaction is complete, lower the system temperature to 65°C, add 15g of phosphorous acid, and stir until completely dissolved. Then, add 15g of a 37% formaldehyde solution dropwise over 30 minutes using the constant-pressure dropping funnel. After the addition is complete, slowly raise the system temperature to 100°C and reflux at this temperature for 4 hours. After the reaction was complete, heating was stopped, and the solution was allowed to cool naturally to room temperature, yielding a pale yellow, transparent polymer aqueous solution. Analysis showed that the solid content of the solution was 35.2 wt%, and the number-average molecular weight (Mn) of the polymer was 3500 g / mol.

[0035] Preparation Example 2: Preparation of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA): The basic operating steps and raw material amounts were the same as in Preparation Example 1, except that the amount of ammonium persulfate initiator was reduced to 10 g; and the copolymerization temperature was controlled at 90°C. All other reaction conditions, grafting reaction steps, and raw material amounts were the same as in Preparation Example 1. After the reaction was completed, the solution was cooled to room temperature to obtain a pale yellow, transparent polymer aqueous solution. Analysis showed that the solid content of the solution was 35.5 wt%, and the number-average molecular weight (Mn) of the polymer was 7500 g / mol.

[0036] Preparation Example 3: Preparation of N,N-diethylaminomethylbenzotriazole (BTA-DEAM): In a 500 mL three-necked flask equipped with a mechanical stirrer, thermometer, and constant-pressure dropping funnel, 119 g (1.0 mol) of benzotriazole and 80 g (1.1 mol) of diethylamine were dissolved in 200 mL of isopropanol and stirred to form a homogeneous solution. The reaction flask was placed in an ice-water bath until the internal temperature dropped below 5 °C. 90 g (1.1 mol) of a 37% formaldehyde aqueous solution was slowly added dropwise over 2 hours through the constant-pressure dropping funnel, with the internal temperature strictly controlled to not exceed 15 °C during the addition. After the addition was complete, the ice-water bath was removed, and the reaction system was allowed to continue stirring at room temperature (25 °C) for 20 hours. After the reaction was complete, the reaction solution was transferred to a rotary evaporator and distilled under reduced pressure at 60 °C and -0.09 MPa to remove the solvent isopropanol and unreacted raw materials. The final product was a pale yellow oily liquid, namely N,N-diethylaminomethyl-benzotriazole.

[0037] Examples 1-3: Example 1: In a reaction vessel, 250 g of the phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA) aqueous solution prepared in Preparation Example 1 was added, followed by 40 g of a 60% (w / w) aqueous solution of hydroxyethylidene diphosphonic acid (HEDP), 80 g of a 50% (w / w) aqueous solution of aminotrimethylene phosphonic acid (ATMP), and 5 g of N,N-diethylaminomethyl-benzotriazole (BTA-DEAM) prepared in Preparation Example 3. Stirring was started until all components were completely dissolved and mixed uniformly. The pH of the mixture was slowly adjusted to 8.5 using a 30% (w / w) sodium hydroxide solution to obtain the anionic polyelectrolyte prepolymer (solution A).

[0038] In another reactor, 20 g of γ-aminopropyltriethoxysilane (γ-APS) was added to 100 g of deionized water. While stirring, the pH of the system was adjusted to 3.5 using a 10% hydrochloric acid solution, and the mixture was stirred continuously at this pH for 30 minutes to carry out hydrolysis. Subsequently, 30 g of zinc sulfate heptahydrate was pre-dissolved in 50 g of deionized water, and the resulting zinc sulfate solution was slowly pumped into the above γ-APS hydrolysate. After stirring until homogeneous, the cationic complex prepolymer (solution B) was obtained.

[0039] 10g of polyoxyethylene-polyoxypropylene block copolymer (L64) was dissolved in 100g of deionized water and stirred until completely dissolved to obtain a thermosensitive co-assembled medium (C solution).

[0040] Formation of thermosensitive polyelectrolyte complex (T-PEC): Add the C solution obtained in step 3 to the reactor containing the A solution, mix thoroughly, and adjust the system temperature to 20°C. Start high-speed stirring, and use a metering pump to uniformly add the B solution obtained in step 2 dropwise to the reactor over 30 minutes. During the dropwise addition, monitor the system in real time and use dilute sodium hydroxide solution to maintain the pH value within the range of 7.0-7.5. After the dropwise addition is complete, continue stirring for 30 minutes for maturation. Finally, add deionized water to make up the remaining amount, so that the total weight of the product is 1000g. The final product is the scale and corrosion inhibitor for seawater circulating cooling water in this embodiment.

[0041] Example 2: In a reaction vessel, 300g of an aqueous solution of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA) prepared in Preparation Example 1 (with a monomer MA to AA molar ratio of 3:7) was added sequentially. Then, 50g of a 60% (w / w) aqueous solution of hydroxyethylidene diphosphonic acid (HEDP), 120g of a 50% (w / w) aqueous solution of aminotrimethylene phosphonic acid (ATMP) (at this point, the solid content mass ratio of HEDP to ATMP was 1:2), and 10g of N,N-diethylaminomethyl-benzotriazole (BTA-DEAM) prepared in Preparation Example 3 were added. Stirring was started until all components were completely dissolved and mixed uniformly. Using a 30% (w / w) sodium hydroxide solution, the pH of the mixture was slowly adjusted to 9.0 to obtain the anionic polyelectrolyte prepolymer (solution A).

[0042] In another reactor, 35g of γ-aminopropyltriethoxysilane (γ-APS) was added to 150g of deionized water. The pH of the system was adjusted to 4.0 with 10% hydrochloric acid solution while stirring, and the mixture was continuously stirred at this pH for 45 minutes for hydrolysis. Subsequently, 45g of zinc sulfate heptahydrate was pre-dissolved in 80g of deionized water, and the resulting zinc sulfate solution was slowly pumped into the above γ-APS hydrolysate. After stirring until homogeneous, the cationic complex prepolymer (solution B) was obtained.

[0043] 25g of polyoxyethylene-polyoxypropylene block copolymer (L64) was dissolved in 150g of deionized water and stirred until completely dissolved to obtain a thermosensitive co-assembled medium (C solution).

[0044] Formation of thermosensitive polyelectrolyte complex (T-PEC): Add the C solution obtained in step 3 to the reactor containing the A solution, mix thoroughly, and adjust the system temperature to 25°C. Start high-speed stirring, and use a metering pump to uniformly add the B solution obtained in step 2 dropwise to the reactor over 20 minutes. During the dropwise addition, monitor the system in real time and use dilute sodium hydroxide solution to maintain the pH value within the range of 7.5-8.0. After the dropwise addition is complete, continue stirring for 45 minutes for maturation. Finally, add deionized water to make up the remaining amount, so that the total weight of the product is 1000g. The final product is the scale and corrosion inhibitor for seawater circulating cooling water in this embodiment.

[0045] Example 3: In a reaction vessel, 350 g of the high molecular weight phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA) aqueous solution prepared in Preparation Example 2 was added. Then, 80 g of a 60% (w / w) aqueous solution of hydroxyethylidene diphosphonic acid (HEDP), 192 g of a 50% (w / w) aqueous solution of aminotrimethylene phosphonic acid (ATMP) (at this point, the solid content mass ratio of HEDP to ATMP was 1:2), and 20 g of N,N-diethylaminomethyl-benzotriazole (BTA-DEAM) prepared in Preparation Example 3 were added sequentially. Stirring was started until all components were completely dissolved and mixed uniformly. Using a 30% (w / w) sodium hydroxide solution, the pH of the mixture was slowly adjusted to 9.5 to obtain the anionic polyelectrolyte prepolymer (solution A).

[0046] In another reactor, 50 g of γ-aminopropyltriethoxysilane (γ-APS) was added to 200 g of deionized water. The pH of the system was adjusted to 4.5 with 10% hydrochloric acid solution while stirring, and the mixture was continuously stirred at this pH for 60 minutes for hydrolysis. Subsequently, 60 g of zinc sulfate heptahydrate was pre-dissolved in 100 g of deionized water, and the resulting zinc sulfate solution was slowly pumped into the above γ-APS hydrolysate. After stirring until homogeneous, the cationic complex prepolymer (solution B) was obtained.

[0047] 40g of polyoxyethylene-polyoxypropylene block copolymer (L64) was dissolved in 200g of deionized water and stirred until completely dissolved to obtain a thermosensitive co-assembled medium (C solution).

[0048] Formation of thermosensitive polyelectrolyte complex (T-PEC): Add the C solution obtained in step 3 to the reactor containing the A solution, mix thoroughly, and adjust the system temperature to 30°C. Start high-speed stirring, and use a metering pump to uniformly add the B solution obtained in step 2 dropwise to the reactor over 15 minutes. During the dropwise addition, monitor the system in real time and maintain the pH value at 8.0 using dilute sodium hydroxide solution. After the dropwise addition is complete, continue stirring for 60 minutes for maturation. Finally, add deionized water to make up the remaining amount, bringing the total product weight to 1000g. This yields the scale and corrosion inhibitor product for seawater circulating cooling water in this embodiment.

[0049] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the difference is that instead of using the stepwise preparation process of liquid A, liquid B, liquid C and temperature-sensitive co-assembly, all raw material components except water in Example 2 are added to the reactor at room temperature at one time and subjected to simple physical mixing and stirring until a homogeneous solution is formed.

[0050] Comparative Example 2: Compared with Example 2, the difference is that in the preparation step of the cationic complex prepolymer (Liquid B), the pH is not adjusted to acidity and the subsequent stirring hydrolysis process is not carried out. Instead, γ-aminopropyltriethoxysilane (γ-APS) is directly added to water and then immediately pumped into zinc sulfate solution for mixing.

[0051] Comparative Example 3: The difference from Example 2 is that, in the preparation process, no thermosensitive co-assembly medium (liquid C, i.e., an aqueous solution of polyoxyethylene-polyoxypropylene block copolymer L64) is prepared or added. In the formation step of the thermosensitive polyelectrolyte complex (T-PEC), liquid B is directly added dropwise to liquid A.

[0052] Comparative Example 4: This comparative example uses a scale and corrosion inhibitor formulation that simulates existing conventional technologies. The preparation method is as follows: a 40% (w / w) aqueous solution of polyacrylic acid (PAA, number average molecular weight 4500), a 60% (w / w) aqueous solution of hydroxyethylidene diphosphonic acid (HEDP), and zinc sulfate heptahydrate are physically mixed with water at room temperature in a solid content mass ratio of 20:10:3. This formulation does not contain aminotrimethylenephosphonic acid, γ-aminopropyltriethoxysilane, or N,N-diethylaminomethyl-benzotriazole.

[0053] Comparative Example 5: Compared with Example 2, the difference is that in the preparation of the anionic polyelectrolyte prepolymer (liquid A), an aqueous solution of conventional polyacrylic acid (PAA, number average molecular weight 4500) with equal solids content was used instead of the aqueous solution of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer (PMAA-PA) prepared in Example 1.

[0054] Test Examples 1-5: Test Example 1: This test example aims to evaluate the physical stability of the scale and corrosion inhibitor prepared in the embodiments of the present invention and the samples prepared in the comparative example, especially their anti-precipitation and anti-stratification ability under accelerated aging conditions.

[0055] Experimental steps: Take 100 mL of each of the samples prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, and place them in clean, dry 100 mL stoppered glass bottles, then seal the bottle openings.

[0056] At room temperature, the initial turbidity of each sample was measured using a turbidimeter, and its initial appearance was recorded visually.

[0057] All sealed sample vials were placed in a constant temperature oven at (50±2)℃ for accelerated aging test during thermal storage for 7 days (168 hours).

[0058] After the heat storage is completed, remove all sample vials and allow them to cool naturally to 25°C at room temperature.

[0059] Observe and record the appearance of each sample after cooling using visual inspection, focusing on whether there is stratification, flocculation or sediment.

[0060] After thoroughly shaking the sample (if there is precipitation, only take the supernatant), measure its turbidity again using a turbidimeter.

[0061] The rate of change in turbidity for each sample was calculated using the following formula: Turbidity change rate (%) = [(Turbidity after storage - Initial turbidity) / Initial turbidity] × 100% Experimental data: Table 1. Results of thermal storage stability test of samples Note: The sample of Comparative Example 1 formed a large amount of precipitate immediately after preparation, which is a heterogeneous system, so effective turbidity measurement is not possible.

[0062] in conclusion: The test data in Table 1 show that the samples from Examples 1, 2, and 3 maintained a uniform appearance and a turbidity change rate of less than 7% after storage at 50°C for 7 days. The components of Comparative Example 1 precipitated immediately after mixing, failing to form a stable product. The sample of Comparative Example 2 showed precipitation after heat storage, with a significant increase in turbidity. These results indicate that the preparation process, which involves pre-complexing zinc ions with hydrolyzed silanes and performing stepwise self-assembly, can effectively avoid direct precipitation reactions between active components. This process integrates chemically incompatible components into a kinetically stable liquid phase system, resulting in a product with heat storage stability.

[0063] Test Example 2: This test example aims to verify whether the scale and corrosion inhibitor prepared in the embodiments of the present invention exhibits a change in physical properties triggered by temperature changes in aqueous solution, and to confirm the source of this characteristic by comparing it with a comparative example that does not contain temperature-sensitive components.

[0064] Experimental steps: Sample preparation: Accurately transfer 1.00 mL of the samples prepared in Example 2 and Comparative Example 3 into a 100 mL volumetric flask, dilute to volume with deionized water and shake well to prepare a test solution with a mass concentration of 1.0%.

[0065] Instrument Setup: Connect the jacketed glass sample cell with magnetic stir bar and temperature sensor to the constant temperature water bath circulator. Immerse the turbidimeter's fiber optic probe in the sample cell, ensuring the measurement optical path is not interfered with by air bubbles.

[0066] Temperature measurement: Inject 50 mL of the test solution into the sample cell and start the magnetic stirrer. Set the initial temperature of the constant temperature water bath circulator to 25 °C. After the temperature in the sample cell stabilizes, record the initial turbidity.

[0067] The temperature was programmed to increase from 25℃ to 55℃ at a rate of 2℃ / 5min. After stabilizing for 2 minutes at each temperature point (25, 27, 29, ..., 55℃), the actual temperature and corresponding turbidity value in the sample cell were recorded simultaneously.

[0068] Each sample was measured three times, and the results were averaged.

[0069] Experimental data: Table 2. Test data on the change of turbidity of sample dilution with temperature in conclusion: The test data in Table 2 show that the turbidity of the diluted sample from Example 2 increased sharply in the temperature range of 37°C to 43°C and remained at a high plateau at higher temperatures. The turbidity of the sample from Comparative Example 3 showed a weak, approximately linear increase throughout the entire test temperature range. The abrupt change in turbidity of the sample from Example 2 is consistent with the cloud point (LCST) characteristics of the block copolymer, which serves as a temperature-sensitive co-assembly medium. This data supports the existence of a temperature-triggered physical phase transition mechanism in the product of this invention, a behavior attributed to the introduction of the temperature-sensitive component.

[0070] Test Example 3: This test case aims to evaluate the ability of the scale and corrosion inhibitor prepared in the embodiments of the present invention to inhibit the formation of calcium carbonate scale in high-temperature, high-hardness static water, and to compare its performance with that of several comparative examples.

[0071] Experimental steps: Experimental water sample preparation: Dissolve analytical grade calcium chloride, magnesium chloride, sodium bicarbonate, and sodium chloride in deionized water in a beaker to prepare a solution with a total hardness (calculated as CaCO3) of 550 mg / L (of which Ca... 2+Simulated seawater with a concentration of 240 mg / L, a total alkalinity (calculated as CaCO3) of 600 mg / L, and a chloride ion concentration of 15000 mg / L.

[0072] Sample addition: Take several 250mL stoppered conical flasks and add 100mL of the above-mentioned simulated seawater to each. Set up a blank sample without any treatment agent. Add the samples of Examples 1-3, Comparative Examples 1, 3, and 4 to the remaining conical flasks respectively, so that the final concentration of the treatment agent is 20mg / L.

[0073] Constant temperature scaling: Place all conical flasks in a constant temperature water bath at (80±1)℃ and heat for 10 hours to accelerate the precipitation process of calcium carbonate.

[0074] Sample preparation and determination: After the isothermal period, remove the conical flasks from the water bath and cool them to room temperature. Filter the water samples in each flask using a 0.45 μm filter membrane to remove the generated calcium carbonate precipitate.

[0075] The filtrate was accurately transferred, and the concentration of residual calcium ions in the filtrate was determined by titration with disodium ethylenediaminetetraacetate (EDTA).

[0076] Scale inhibition rate calculation: The scale inhibition rate η of each sample is calculated according to the following formula: η(%)=[(C2-C0) / (C1-C0)]×100% Where, C0 is the calcium ion concentration (mg / L) in the blank sample filtrate; C1 is the initial calcium ion concentration (mg / L) in the simulated seawater before the experiment; C2 is the calcium ion concentration (mg / L) in the experimental sample filtrate with added treatment agent.

[0077] Experimental data: Table 3. Evaluation results of static scale inhibition performance Note: The blank sample does not contain scale inhibitor, and its results are used as the benchmark for calculating the scale inhibition rate, so the scale inhibition rate index is not applicable.

[0078] in conclusion: The test data in Table 3 show that the static scale inhibition rates of Examples 1, 2, and 3 for calcium carbonate all exceed 91%, which is higher than that of the comparative examples. Comparative Example 1, due to component precipitation failure, has a scale inhibition rate close to zero. Comparative Example 3, lacking the temperature-sensitive co-assembled medium, has lower scale inhibition performance than the examples. Comparative Example 4, using a conventional polymer, also has lower scale inhibition performance than the examples of this invention. These results indicate that the specific structure of the copolymer, the multi-component compound system, and the polyelectrolyte composite structure formed through the co-assembly process of this invention are the reasons for its high static scale inhibition performance.

[0079] Test Example 4: This test case aims to simulate the dynamic operating environment of an industrial circulating cooling water system and evaluate the comprehensive scale inhibition and corrosion inhibition performance of the product of the present invention under continuous flow and heat exchange conditions, especially the synergistic protection effect on two typical metal materials, carbon steel and brass.

[0080] Experimental steps: Coupling preparation: 20# carbon steel and H62 brass coupons with dimensions of 50mm × 25mm × 2mm were selected. They were sequentially subjected to degreasing, pickling, neutralization, rinsing with deionized water, dehydration with anhydrous ethanol, and cold air drying. The initial mass of each coupon was accurately weighed using an analytical balance and recorded to the nearest 0.1mg.

[0081] Dynamic simulation device: A set of circulating water dynamic simulation device is adopted, which includes a water storage tank, circulating pump, flow meter, plate test section and a simulated heat exchange tube section with built-in heating rod.

[0082] Experimental parameter settings: The simulated seawater prepared in Test Example 3 was added to the water storage tank. The system operating parameters were set as follows: the circulating water flow rate was 0.5 m / s, the main water temperature was controlled at (45±1)℃, the simulated heat exchange tube surface temperature was controlled at (55±2)℃, and the system concentration factor was maintained at 3.0.

[0083] Experimental Procedure: Pretreated carbon steel and brass plates were installed in the plate test section. The device was started, and after the system stabilized, 50 mg / L of samples from Example 2, Comparative Example 3, and Comparative Example 4 were added to different batches of experimental water. A blank sample without any treatment was also included. The experiment was run continuously for 120 hours.

[0084] Performance evaluation: Corrosion rate determination: After the experiment, the pads were removed. Corrosion products and scale on the surface of the pads were removed using the chemical cleaning method in GB / T18175-2000 standard, followed by rinsing, drying, and weighing. The annual corrosion rate was calculated based on the weight loss of the pads.

[0085] Scaling determination: The simulated heat exchange tube was removed and dried in an oven at 105°C until constant weight. Its mass was accurately measured, and the amount of scale deposited per unit area was calculated by comparing it with the mass before the experiment.

[0086] Experimental data Table 4. Evaluation results of dynamic simulation corrosion and scaling performance in conclusion: Table 4 shows the dynamic simulation test results, indicating that under the conditions of Example 2, the corrosion rates of carbon steel and brass, as well as the amount of scale deposited on the heat exchanger tube surface, were lower than those of the blank sample and the comparative examples. This performance improvement can be attributed to the product's temperature-sensitive characteristics. When circulating water flows through the higher-temperature heat exchange surface, it triggers a phase change in the polyelectrolyte complex, leading to an increase in the concentration of the active component in that region, thereby achieving a more effective scale inhibition and corrosion inhibition effect at the heat exchange interface. The performance data of Comparative Example 3, which lacks the temperature-sensitive component, also indirectly supports this explanation.

[0087] Test Example 5: This test example aims to directly verify the temperature-sensitive targeted enrichment behavior of the active components in the product of this invention by quantitatively analyzing the deposition amount of corrosion-inhibiting components on the surface at different temperatures.

[0088] Experimental steps: Experimental setup construction: A micro-circulation loop consisting of a room temperature section and a local heating section was constructed. The room temperature section maintains the water temperature at (25±1)℃ through natural convection; the heating section uses an external heating jacket to precisely control the inner wall surface temperature at (50±1)℃.

[0089] Hanger placement: Pre-treated and weighed 20# carbon steel hangers are pre-placed inside the ambient temperature section and the heating section respectively.

[0090] Experimental procedure: Simulated seawater containing 200 mg / L of the sample from Example 2 and 200 mg / L of the sample from Comparative Example 3 was prepared. The prepared solutions were injected into the micro-circulation loops, and the circulation pumps were started to circulate the solutions in the loops at a low speed for 2 hours.

[0091] Sample collection and processing: After the experiment, stop the circulation and carefully remove all the trays. Gently rinse the surface of the trays with plenty of deionized water to remove any loosely adhered substances.

[0092] Place each tablet in a clean beaker, add 10 mL of 2% dilute nitric acid solution, and sonicate for 15 minutes to completely wash away the deposits on the surface of the tablet.

[0093] Collect all the eluent and bring the volume to 25 mL with deionized water in a volumetric flask.

[0094] Elemental analysis: The concentration of zinc (Zn) in each eluent was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the amount of zinc deposited per unit area of ​​the substrate was calculated accordingly.

[0095] Experimental data Table 5. Analysis results of zinc deposition on the surface of the pads Example 2 Heating section (50℃) 15.8 Example 2 Normal temperature section (25℃) 1.9 Comparative Example 3 Heating section (50℃) 3.2 Comparative Example 3 Normal temperature section (25℃) 2.9 in conclusion: The data in Table 5 show that when using the sample from Example 2, the zinc deposition on the surface of the heating section (50°C) plate was 15.8 μg / cm³. 2 The deposition rate was significantly higher than that at room temperature (25℃) (1.9 μg / cm³). 2 For Comparative Example 3, which does not contain the temperature-sensitive component, there was no significant difference in zinc deposition between the heated and room-temperature sections. The selective enrichment of zinc on high-temperature surfaces, as a marker of the corrosion inhibition system, is consistent with the temperature-sensitive targeted delivery mechanism proposed in this invention. This result indicates that the polyelectrolyte composite structure of the product tends to deposit on high-temperature surfaces above its phase transition temperature.

Claims

1. A method for preparing a scale and corrosion inhibitor for seawater circulating cooling water, characterized in that, The scale and corrosion inhibitor for seawater circulating cooling water is made from raw materials comprising the following parts by weight: 100-115 parts of phosphonic acid-grafted maleic anhydride-acrylic acid copolymer; 28-40 parts of hydroxyethylidene diphosphonic acid; 50-75 parts of aminotrimethylenephosphonic acid; 8-15 parts of N,N-diethylaminomethyl-benzotriazole; 30-45 parts of γ-aminopropyltriethoxysilane; 40-55 parts zinc salt; 20-35 parts of polyoxyethylene-polyoxypropylene block copolymer; The phosphonic acid-grafted maleic anhydride-acrylic acid copolymer is prepared by the following steps: After maleic anhydride and acrylic acid are copolymerized, phosphorous acid and formaldehyde are added for grafting reaction, thereby introducing phosphonic acid groups into the copolymer molecular chain. The N,N-diethylaminomethyl-benzotriazole is prepared by benzotriazole, diethylamine and formaldehyde under Mannich reaction conditions; The scale and corrosion inhibitor for seawater circulating cooling water is prepared through the following steps: (a) The phosphonic acid-grafted maleic anhydride-acrylic acid copolymer, hydroxyethylidene diphosphonic acid, aminotrimethylene phosphonic acid and N,N-diethylaminomethyl-benzotriazole are mixed, and the pH of the mixture is adjusted to 8.5-9.5 to form an anionic prepolymer; (b) The γ-aminopropyltriethoxysilane is hydrolyzed under acidic conditions of pH 3.5-4.5 for 30-60 minutes and then complexed with the zinc salt to form a cationic complex prepolymer; (c) In the presence of the polyoxyethylene-polyoxypropylene block copolymer, at a temperature of 20-30°C, the cationic complex prepolymer obtained in step (b) is added to the anionic prepolymer obtained in step (a), and the pH value of the system is maintained in the range of 7.0-8.0 during the addition process to form a polyelectrolyte complex.

2. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The phosphonic acid-grafted maleic anhydride-acrylic acid copolymer is obtained by polymerization of maleic anhydride and acrylic acid as comonomers, wherein the molar ratio of maleic anhydride to acrylic acid in the comonomer is (2-4):(6-8).

3. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The mass ratio of the total solid content of the phosphonic acid-grafted maleic anhydride-acrylic acid copolymer to that of the hydroxyethylidene diphosphonic acid and the aminotrimethylene phosphonic acid is (0.85-1.4):

1.

4. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The zinc salt is zinc sulfate or zinc sulfate heptahydrate.

5. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The turbidity point temperature of the polyoxyethylene-polyoxypropylene block copolymer in aqueous solution is 35-50℃.

6. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The solid content mass ratio of the hydroxyethylidene diphosphonic acid to aminotrimethylene phosphonic acid is 1:(1.6-2.1).

7. The method for preparing a scale and corrosion inhibitor for seawater circulating cooling water according to claim 1, characterized in that, The weight ratio of the γ-aminopropyltriethoxysilane to the zinc salt is 1:(1.2-1.5).

Citation Information

Patent Citations

  • Composite corrosion and scale inhibitor for power plant circulating cooling water system based on reclaimed water

    CN111573859A

  • Composite corrosion and scale inhibitor and its application in treating circulating cooling water

    CN1618743A